Best Answer

We're not sure what the question means by "root". It may be what's usually

referred to as the "solution" of the equation ... the number that 'a' must be in

order to make the equation a true statement. Here's how to find the 'solution':

- 5a - 3 = 3a

Add 5a to each side:

- 3 = 8a

Divide each side by 8:

- 3/8 = a

Q: What is the root of -5a - 3 equals 3a?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

13a - 6 + a = 5a + 3 + 3a 13a + a - 5a - 3a = 3 + 6 6a = 9 6a/6 = 9/6 a = 3/2

9a2=24a-16 9a2-24a+16=0 (3a-4)(3a-4)=0 3a-4=0 a=4/3 double root

(3 x 3) - 6 = 3 3a-6=3 3a=3+6 3a=9 a=9/3 a=3

3a = 1a = 1/3 (a third)

(5a).7 = -23 7(5a) = -23 35a = -23 a = -23/35 a= -0.657 (3 d.p.)

Related questions

If 3a+5=5a+3, then: 3a+5 - 3a = 5a+3 - 3a 5=2a+3 5 - 3=2a+3 - 3 2=2a a=1

Answer to: 5a + 1 = a - 3a = -1

13a - 6 + a = 5a + 3 + 3a 13a + a - 5a - 3a = 3 + 6 6a = 9 6a/6 = 9/6 a = 3/2

a + b + c = 180 b = 3a c = 5a Substituting the values of b and c into the first equation. a + 3a + 5a = 180 or 9a = 180 so that a = 20 then b = 3a = 3*20 = 60 and c = 5a = 5*20 = 100

-8a + 3a = (-8 + 3)a = (5)a = 5a

5a times 3a minus 8a = (5*3)*a2 - 8a = 15a2 - 8a

5a - 5 = 7 + 2a ( subtract 2a from both sides) 3a - 5 = 7 (add 5 to both sides) 3a = 12 ( divide both sides by 3) a = 4

what is 5a x 3 x 2b

3a2 - 16a + 5 = 3a2 - 15a - a + 5 = 3a(a -5) - 1(a -5) = (3a - 1)(a - 5)

9a2=24a-16 9a2-24a+16=0 (3a-4)(3a-4)=0 3a-4=0 a=4/3 double root

(3 x 3) - 6 = 3 3a-6=3 3a=3+6 3a=9 a=9/3 a=3

Three consecutive even integers can be represented by a-2, a & a+2.Five times the first is 5a-10. Three times the second is 3a.5a-10 is 14 more than 3a, so 5a-10 = 3a+14Adding 10 to both sides: 5a = 3a+24Taking 3a from both sides: 2a = 24Therefore a=12The three consecutive even integers are 22, 24 and 26.